2016
DOI: 10.1111/jog.12968
|View full text |Cite
|
Sign up to set email alerts
|

Transfemoral temporary aortic balloon occlusion in surgical treatment of second trimester intramural ectopic pregnancy

Abstract: Intramural ectopic pregnancy is a rare type of ectopic pregnancy that may lead to life-threatening hemorrhage. In the present case, a 20-year-old woman at 18.5 weeks of gestation, G P , was diagnosed with intramural ectopic pregnancy on ultrasound and magnetic resonance imaging, which showed a 14-cm × 14-cm gestational sac on the right posterior lateral side of the uterus fundus, surrounded completely by myometrium. Considering the increased risk of bleeding during surgery, transfemoral temporary aortic balloo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 9 publications
0
7
0
1
Order By: Relevance
“…The probability of hysterectomy has decreased in recent years (75% of hysterectomy reported before the 2010s), which may be attributed to early diagnosis and progress in management. Some patients in their second trimester were treated with a combination of aorta balloon occlusion or uterine artery embolization (7,12). Hence, it may be advisable that patients with a high risk of hysterectomy develop a prearranged plan and undergo a more comprehensive preoperative evaluation and procedures such as uterine artery embolization, uterine artery ligation, and aorta balloon occlusion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The probability of hysterectomy has decreased in recent years (75% of hysterectomy reported before the 2010s), which may be attributed to early diagnosis and progress in management. Some patients in their second trimester were treated with a combination of aorta balloon occlusion or uterine artery embolization (7,12). Hence, it may be advisable that patients with a high risk of hysterectomy develop a prearranged plan and undergo a more comprehensive preoperative evaluation and procedures such as uterine artery embolization, uterine artery ligation, and aorta balloon occlusion.…”
Section: Discussionmentioning
confidence: 99%
“…These non-specific symptoms can sometimes lead to the misdiagnosis of intramural ectopic pregnancy as myoma, or choriocarcinoma (6). Besides, in previous studies, some patients experiencing intramural ectopic pregnancies reported no discomfort (7), and even the serum β-HCG was negative in one reported case (8). Due to the rarity of intramural ectopic pregnancy, data comprising mainly of case reports on the clinical characteristics, treatment options, and subsequent fertility outcomes in patients are limited.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, surgical strategy theoretically increases the danger of uterine rupture in the event of a future pregnancy. Furthermore, uterine artery embolization (UAE) and temporary balloon occlusion have been confirmed effective in embryo atrophy and absorption as well [14].…”
Section: Discussionmentioning
confidence: 99%
“…Some of cases were not found until the rupture of the conception [6,10]. There are a few reports that intramyometrial pregnancy lasts longer than 12 weeks' gestation [12,[24][25][26][27]. With no early recognition and treatment, the gestational sac grows to bulge from the serosal surface of the uterus with progressive thinning of the myometrium.…”
Section: Discussionmentioning
confidence: 99%
“…The main concern with laparoscopic treatment of intramural pregnancy is the subsequent risk of uterine rupture and the recurrence of ectopic pregnancy, which happened to the patient in our case. Transfemoral temporary aortic balloon occlusion, reversible Hem-o-Lok clip occlusion of uterine artery and uterine artery embolization (UAE) have also been reported to prevent extensive bleeding [17,26,[33][34][35][36]. Nevertheless, special attention must be paid to reduce complications such as ischemia, reperfusion injury and thromboembolism [37].…”
Section: Discussionmentioning
confidence: 99%